Analisis Fungsi Joshi Dake dalam Manga Kimetsu no Yaiba Karya Koyoharu Gotouge - Susanti, Maria; Putri, Meira Anggia (Universitas Negeri Padang, 2024)
The writing discussed analysis function of dake in manga Kimetsu no Yaiba by Koyoharu Gotouge. The writer chose the title due to the lack of explanation of those words in Japanese books, therefore there were still many mistakes in using dake. In Sutedi (2018), Dake had 12 functions in the sentence, but only 4 function were found in this study. This type of research is a qualitative research with descriptive method. The function of dake shows limitations, levels, habits, and affirmation of another.